Does bridging radiation therapy affect the pattern of failure after CAR T-cell therapy in non-Hodgkin lymphoma?. (January 2022) - Saifi, Omran; Breen, William G.; Lester, Scott C.; Rule, William G.; Stish, Bradley; Rosenthal, Allison; Munoz, Javier; Herchko, Steven M.; Murthy, Hemant S.; Lin, Yi; Bansal, Radhika; Hathcock, Matthew A.; et al.
Graphical abstract: Highlights: Majority of progressions (88%) after CAR T-cell therapy for non-Hodgkin lymphoma have local component. Bridging radiotherapy achieves excellent in-field local control (86% at 1-year). In-field recurrences are characterized by bulky disease, SUVmax >20, elevated LDH and extranodal involvement pre-CART infusion. Abstract: Purpose: Analyze the pattern of disease failure after anti-CD19-directed chimeric antigen receptor T-cell therapy (CART) for non-Hodgkin lymphoma, assess the local control rate of bridging radiotherapy (bRT) and characterize in-field recurrences. Methods: We retrospectively reviewed 120 patients with NHL who received CART between 2018 and 2020. Baseline characteristics and treatment outcomes were compared between patients who received bRT and those who did not (noRT). Results: Of the 118 patients included, 14 (12%) received bRT, while 104 (88%) did not. bRT group had more localized and extranodal disease. bRT was delivered with a median dose of 20 Gy (range: 15–36) in 5 fractions (range: 3–24). Pattern of failure analysis revealed that progression involving pre-existing sites was the predominant pattern of failure in both the bRT and noRT groups (86% and 88%, respectively). Median duration of response was 128 days (range: 25–547) for bRT group and 93 days (range: 22–965) for noRT group ( p = 0.78). In the bRT group, only 2/15 sites irradiated had infield recurrence and where characterized by bulky disease, SUVmax >20, elevated LDH at the time of CART infusion, and extranodal involvement. The bRT 1-year LC was 86%. Median duration of local response was 257 days (range: 25–630) for radiation-bridged sites. Conclusion: Majority of progressions after CART infusion involve pre-existing sites. Bridging RT prior to CART provides excellent in-field local control and durable response. Patients with bulky disease, SUVmax >20, elevated LDH, and extranodal involvement are likely at higher risk of in-field recurrence after bRT and may benefit from higher curative doses of bRT.